Long-term plasticity of excitatory inputs onto identified hippocampal neurons in the anaesthetized rat - Lau, P; Petrina, Yau Pok, Lau (2015)
Use-dependent long-term plasticity in synaptic connections represents the cellular substrate for learning and memory. The hippocampus is the most thoroughly investigated brain area for long-term synaptic plasticity, long-term potentiation (LTP) and long-term depression (LTD) are both well characterized in glutamatergic excitatory connections between hippocampal principal cells in vitro and in vivo. An increasing number of studies based on acute brain slice preparations report LTP and LTD in excitatory synapses onto postsynaptic hippocampal GABAergic inhibitory interneurons. However, a systematic study of activity-induced long-term plasticity in excitatory synaptic connections to inhibitory GABAergic interneurons in vivo is missing. To determine whether LTP and LTD occur in excitatory synaptic connections to the hippocampal CA1 area GABAergic interneurons types in intact brain, I have used juxtacellular recording to measure synaptically evoked short-delay postsynaptic action potential probability in identified CA1 neurons in the urethane-anaesthetized rats. Plasticity in excitatory synaptic connections to CA1 cell types was measured as a change of afferent pathway stimulation-evoked postsynaptic spike probability and delay. In the study only experiments with monosynaptic-like short-delay (range 3-12 ms) postsynaptic spikes phase-locked to afferent stimulation were used. Afferent fibres were stimulated from the CA1 area of the hippocampus at the contralateral (left) side to avoid simultaneous monosynaptic activation of GABAergic fibres and to exclude antidromic spikes in recorded CA1 cells (in right hemisphere). Plasticity in pathways was tested using theta-burst high-frequency stimulation (TBS, 100 pulses), which is one of the most common synaptic plasticity induction protocols in acute brain slice studies. I discovered that TBS elicited permanent potentiation in single shock-evoked postsynaptic spike probability with shortening or no change in evoked spike latency in various postsynaptic neuron types including three identified pyramidal cells and parvalbumin-expressing (PV+) interneurons. Most fast-spiking PV+ cells showed LTP including an axo-axonic cell and one bistratified cell, whereas two identified basket cells exhibited LTD in similar experimental conditions. In addition, I discovered diverse plasticity in non-fast spiking interneurons, reporting LTP in an ivy cell, and LTD in three incompletely identified regular-spiking CA1 interneurons. I report that the underlying brain state, defined as theta oscillation (3-6 Hz) or non-theta in local field potential, failed to explain whether LTP, LTD or no plasticity was generated in interneurons. The results show that activity-induced potentiation and depression similar to LTP and LTD also occur in excitatory synaptic pathways to various CA1 interneurons types in vivo. I propose that long-term plasticity in excitatory connections to inhibitory interneurons may be take place in learning and memory processes in the hippocampus.